Religion and Social Capital: Examining the Roles of Religious Affiliation and Salience on Parental Network Closure. Issue 2 (3rd May 2016) - Park, Julie J.; Sharma, Gitima
ABSTRACT: Social capital consists of relational ties and networks that can foster social norms, provide support, and be leveraged for gain. Numerous studies indicate that social capital can positively influence educational achievement. Prominent scholar Robert Putnam has noted that religion is a top source of social capital, yet few studies examine variation in levels of social capital for students of different religious backgrounds, leaving unanswered questions about the role of religion in shaping social capital. This study seeks to extend the research on religion and social capital by examining how religious salience and affiliation are related to social capital among a national sample of college students. It specifically examines parental network closure (a measure of social capital that reflects the closeness of one's social relationships), which has been linked to academic achievement, self-esteem, and self-efficacy. Results indicate that Hindu students have higher levels of parental network closure, while students with no religious affiliation have significantly lower levels. Students with higher religiosity also have higher parental network closure regardless of affiliation. Implications are discussed.